Dissociable roles of the hippocampus and parietal cortex in processing of coordinate and categorical spatial information - Baumann, Oliver; Mattingley, Jason B. (Frontiers in Human Neuroscience, 2014)
It is generally accepted that spatial relationships and spatial information are critically involved in the formation of cognitive maps. It remains unclear, however, which properties of the world are explicitly encoded and how these properties might contribute to the formation of such maps. It has been proposed that spatial relations are encoded either categorically, such that the relative positions of objects are defined in prepositional terms; or as visual coordinates, such that the precise distances between objects are represented. Emerging evidence from human and animal studies suggests that distinct neural circuits might underlie categorical and coordinate representations of object locations during active spatial navigation. Here we review evidence for the hypothesis that the hippocampal formation is crucial for encoding coordinate information, whereas the parietal cortex is crucial for encoding categorical spatial information. Our short review provides a novel view regarding the functions and potential interactions of these two regions during active spatial navigation.